2006
DOI: 10.1179/146532806x120318
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis in children from Kuala Lumpur, Malaysia

Abstract: There are few data on paediatric melioidosis in endemic areas outside rural north-eastern Thailand and northern Australia. This study reports 16 culture-confirmed cases of melioidosis in children aged < or = 15 years seen between 1976 and 2005 at an urban teaching hospital in Kuala Lumpur, Malaysia. Seven (43.8%) patients had septicaemic melioidosis (with three known deaths) and nine (56.2%) had localised disease (one death). Eleven (68.8%) patients had underlying diseases, including five with haematological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Childhood melioidosis is predominantly a disease of apparently immunocompetent persons, which contrasts with disease in adulthood when at least 80% of those affected have at least one risk factor that affects host immunity. Our finding that two-thirds of disease was localized is consistent with the published literature from Asia,30–34 and the proportion of localized infections in the region of the head and neck is also consistent 31,33. A previous report describing acute suppurative parotitis in children caused by B. pseudomallei in northeast Thailand suggested that this syndrome may prove to be a sensitive indicator of the presence of melioidosis within a given geographic area 9.…”
Section: Discussionsupporting
confidence: 91%
“…Childhood melioidosis is predominantly a disease of apparently immunocompetent persons, which contrasts with disease in adulthood when at least 80% of those affected have at least one risk factor that affects host immunity. Our finding that two-thirds of disease was localized is consistent with the published literature from Asia,30–34 and the proportion of localized infections in the region of the head and neck is also consistent 31,33. A previous report describing acute suppurative parotitis in children caused by B. pseudomallei in northeast Thailand suggested that this syndrome may prove to be a sensitive indicator of the presence of melioidosis within a given geographic area 9.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, only 3% of children in the Cambodian study had significant co-morbidity [26]. In contrast, 41% of children with melioidosis in Sabah (another Malaysian Bornean state), the majority of whom were ethnic Kadazandusuns, had β-thalassemia major, while 31% of children in Kuala Lumpur (in peninsular Malaysia) had hematological malignancies [14, 32]. Five (12%) children in our study had moderate or severe anemia at presentation (hemoglobin 6.4–7.8 g/dL).…”
Section: Discussionmentioning
confidence: 99%
“…Similar paediatric case reviews have been completed, for example in Australia (45 cases between 1989 and 2013 [15] and 8 cases between 1996 and 2006 [23]), India (11 cases from 2007 to 2014 [22]) Malaysia (16 cases between 1976 and 2005 [24] and 13 cases between 2000 and 2003 [25]), Singapore (17 children between 2002 and 2014) [26] and Thailand (55 cases between 1979 and 1993 [27], 37 localised cases between 1994 and 2006 [28], and 46 cases between 1990 and 1991 [29]). Broadly the findings are similar in all studies.…”
Section: Discussionmentioning
confidence: 99%